Porous composite medium as well as preparation method and application thereof
The porous composite media formed by sintering polyethylene and other polymer material fibers solves the problems of low flux and insufficient mechanical strength of porous composite media in the prior art, and achieves both high throughput and high mechanical properties, which are suitable for multiple filtering applications.
Patent Information
- Application Number
- CN202411382750.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-14
AI Technical Summary
The existing polymer porous composite media have shortcomings in filtration speed and mechanical strength, low flux and easy to lose powder, or poor mechanical strength, which limits its application in gas and liquid filtration.
Using porous composite media formed by sintering of polyethylene and other polymer material fibers, the flux and mechanical properties of the medium are improved by selecting the appropriate polymer fiber diameter and porosity, combined with the formation of agglomerates, and the flux and mechanical properties of the medium are enhanced to ensure high porosity and Both high mechanical strength.
It achieves high throughput and excellent mechanical properties, ensuring fast filtration speed, high cleanliness and long service life, and is suitable for filtration applications in a variety of harsh environments.
Smart Images

Figure CN119303380A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a porous composite medium and a preparation method and application thereof. Background Art
[0002] The polymer porous composite medium is a porous composite medium made of high molecular polymers (such as polyolefins, polyesters, etc.), which can be used as filter materials (such as filter elements), adsorption materials, various carriers (such as catalyst carriers), etc. The polymer porous composite medium also has the characteristics of acid resistance, alkali resistance and corrosion resistance of other organic solvents, as well as high strength and good temperature resistance, so that it can maintain high efficiency in filtering and adsorption in various harsh environments. These characteristics make the polymer porous composite medium an important component in equipment in the fields of water treatment and gas treatment, and can also be used as a carrier support in the field of biomedical engineering, and can be used as a carrier or filter material or adsorption material in the chemical industry, etc., and has broad application prospects.
[0003] A main preparation method of polymer porous composite media is powder sintering method, the main step is to press the powder into a green compact, heat it to a temperature lower than the melting point of the main component, and obtain the material or product with the required strength and characteristics due to physical and chemical effects such as bonding between particles. CN102553353A provides a microporous filter medium, which is formed by adding a composite material to a polymer polyethylene powder and sintering it; the composite material forms a mesh-like flexible bone between the polymer polyethylene powder to support the bonding structure of the polymer polyethylene powder. Compared with the porous composite medium material prepared by the phase inversion method, for example, the porous composite medium material prepared by the sintering method can usually prepare a porous composite medium material with a complex shape and structure, and has higher mechanical strength. At the same time, the sintering process can make the microstructure inside the porous composite medium material more uniform, reduce defects and impurities, but the porosity in the obtained porous filter element is relatively low, generally only 20-40%, resulting in a low flux of the porous composite medium and a slow filtration speed; in addition, it is easy to lose powder, affecting the cleanliness.
[0004] Another common preparation process of polymer porous composite media is to prepare multilayer polymer materials by hot pressing or ultrasonic pressing. For example, CN101559326A provides a nanofiber ultrafiltration membrane and a preparation method thereof, comprising the following steps: (1) one or two polymer spinning solutions are respectively passed through one or two spinnerets and sprayed onto a horizontally moving receiving roller for electrostatic spinning. During the spinning process, the weight concentration of the spinning solution gradually decreases to obtain an electrostatically spun non-woven fabric; (2) then hot pressing is performed to obtain a nanofiber ultrafiltration membrane. This preparation method can produce a material with a higher porosity, but the mechanical strength is poor, the industrial applicability is poor, and the application scenarios are severely limited.
[0005] Therefore, it is urgent to develop a porous composite medium with high throughput and excellent mechanical strength. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a porous composite medium which can combine high flux and excellent mechanical strength (high hardness and compressive strength), is suitable for use as a porous composite medium for gas filtration and liquid filtration, and has broad application prospects.
[0007] In order to achieve the above-mentioned object, the present invention adopts the following technical scheme: a porous composite medium, the porous composite medium comprises polymer fibers for forming a porous structure, the polymer constituting the polymer fibers comprises polyethylene (PE) and polymer A, the polymer A comprises at least one of polypropylene (PP), polyethylene terephthalate (PET), polyamide (PA), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), and the SEM average diameter of the polymer fibers is 5 μm-40 μm (for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm);
[0008] There are several agglomerates formed by sintering the polymer fibers in the porous composite medium; the PMI average pore size of the porous composite medium is 0.1μm-5μm (for example, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm), and the porosity is 40%-80% (for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%).
[0009] The porous composite medium of the present invention is sintered with high molecular polymer fibers as raw materials; compared with powder sintering, the medium formed by fiber sintering is more conducive to obtaining higher porosity and higher flux. On this basis, instead of selecting a single polymer, at least two high molecular polymers are selected as raw materials, that is, the polymer constituting the polymer fiber includes polyethylene (PE) and polymer A, wherein PE acts as a binder and polymer A acts as a supporting skeleton. Such a composition is conducive to the formation of agglomerates (while a single polymer is difficult to form the agglomerates required by the present invention), so that the product has excellent flux (air permeability or liquid flux) and mechanical strength, and also solves the problem of poor heat shrinkage resistance of a single polymer such as pure PP.
[0010] Moreover, compared with a single polymer, polymer A in the composition of the composite medium can give the product different characteristics and can be applied to different application scenarios. For example, when polymer A is PP, the porous composite medium will have higher temperature resistance and wear resistance; and for example, compared with PP, when polymer A is PET, it is more conducive to further improving the hardness of the composite medium when combined with PE. PA combined with PE can prepare a composite medium that has both the softness and chemical resistance of PE and the high strength and wear resistance of PA. PBT is a variant of PET with similar chemical stability and thermoplasticity, and some physical properties are slightly different. The composite medium containing PE / PBT may combine the flexibility of PE and the specific performance advantages of PBT. PTT has excellent heat resistance, chemical resistance and good elasticity, and the porous composite medium obtained by combining with PE has higher heat resistance and elasticity. It should be understood that in order to improve the performance, inorganic fibers such as glass fibers, carbon fibers, etc. can also be doped in the porous composite medium to prepare a composite medium with high strength, high modulus or special functionality.
[0011] The average pore size of PMI can reflect the size of the overall pore size of the porous composite medium to a certain extent. The larger its value is, the larger the overall pore size of the composite medium is; the size of its value greatly affects the flux size of the porous composite medium and the interception efficiency of various impurities. In the present invention, the composite medium sintered by using at least two polymer raw materials has a PMI average pore size of 0.1μm-5μm, that is, the composite medium is a micron-level porous composite medium, and the pores are relatively large, but not too large. Its performance is essentially different from that of nano-level porous composite media and fabrics with visible pores. The average pore size of PMI can be obtained by testing with a PMI pore size tester; the porous composite medium of the present invention can be cylindrical, rectangular, or other shapes required by customers. The porous composite medium includes two end faces (external surfaces), and the average pore size of PMI is the corresponding PMI pore size measured from one end face of the medium to the other end face.
[0012] The porosity test method of the present invention is the mercury injection method. Those skilled in the art can also obtain the porosity by other measuring methods. The above measuring methods are for reference only. After the mercury injection method test, the porosity of the porous composite medium of the present invention is 40%-80%, indicating that the porosity of the composite medium is relatively large and the number of holes is large, which is conducive to making the porous composite medium have a high flux as a whole. Under the synergistic effect of the PMI average pore size and porosity of the composite medium, it is ensured that the composite medium has a high flux, a fast filtration speed, and a high dirt holding capacity, which can intercept and accommodate more impurity particles and has a long service life.
[0013] In general, if the pores of a porous composite medium are large and the porosity is large, then its mechanical strength is generally very low, especially under high pressure, the pores are easy to shrink or collapse, and the service life is short; in the present invention, it is found that the composite medium has a high mechanical strength (its hardness and compressive strength are both high) while having a high porosity and a large pore size. When observing its microstructure, it was unexpectedly found that there were several agglomerates in the porous composite medium (the number of agglomerates is not less than 2). The appearance of these agglomerates is probably because on the basis of using at least two fiber raw materials, under the action of sintering, the contact points between the polymer fibers begin to bond, so that the originally dispersed fibers are closely combined together, and gradually expand to form relatively dense sintered agglomerates; the agglomerates obtained by sintering are relatively dense, which can greatly enhance the mechanical properties of the porous composite medium. At the same time, the study found that the presence of agglomerates makes it difficult for the composite medium to be stratified, and it is even less likely to fall off powder, fibers or particles. The product quality is highly stable and the cleanliness of the material to be filtered is greatly guaranteed.
[0014] In the porous composite medium described in the present invention, under the synergistic effect of agglomerates and free fibers of a certain thickness (there are a certain number of agglomerates and a certain number of relatively free polymer fibers in the composite medium), non-directional tortuous pathways are formed (the non-directional tortuous pathways refer to randomly oriented groove structures and / or discretely distributed pore structures, and the non-directional tortuous pathways are interconnected), ensuring that the composite medium can fully and effectively retain impurity particles of a certain particle size (mainly micron-sized impurities) with high retention efficiency.
[0015] The SEM average diameter of the polymer fibers in the composite medium and the subsequent characteristics of the agglomerates can be measured by using a scanning electron microscope to characterize the morphology of the cross section of the composite medium, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually, and performing corresponding calculations.
[0016] When actually measuring, the cross section (thickness direction) of the composite medium can be characterized by an electron microscope to obtain the corresponding SEM image. Since the distribution of polymer fibers and aggregates is roughly uniform, a certain area can be selected, such as 1mm 2 (1mm x 1mm) or 10000μm 2 (100 μm multiplied by 100 μm), the specific area size depends on the actual situation, and then the polymer fiber diameter and various characteristics of the agglomerates on the area are measured by corresponding computer software or manually, and several tests are carried out (preferably more than 10 times, the specific number of times depends on the situation), and the average value is taken to obtain the SEM average diameter of the polymer fiber and the average value of various characteristics of the agglomerates; of course, technical personnel in this field can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only.
[0017] As a further improvement of the present invention, the SEM average diameter of the polymer fiber is 8 μm-35 μm; and / or the PMI average pore size of the porous composite medium is 0.3 μm-3.5 μm;
[0018] And / or, the porosity of the porous composite medium is 45%-75%.
[0019] Fibers of appropriate thickness can provide mechanical strength for porous composite media, and can also provide a certain adsorption effect, further improve the interception efficiency, and fully capture various substances. The thickness of the polymer fiber will affect the stability of the pores in the porous composite medium. When the fiber diameter is large, it has higher mechanical strength, especially it is not easy to break or deform under high pressure, avoiding the shrinkage or collapse of the pores, thereby ensuring that high flux is maintained during long-term use, thereby making the product have a longer service life. When the range of the PMI average pore size, porosity and fiber diameter of the porous composite medium is met at the same time, under their synergistic effect, the composite medium can fully and effectively intercept impurity particles (mainly micron-level impurities) of a certain particle size, which is conducive to further improving the interception efficiency and flux stability of the porous composite medium, while ensuring that the porous composite medium has excellent mechanical properties, and significantly improving the hardness and compressive strength of the porous composite medium.
[0020] As a further improvement of the present invention, in the cross section of the porous composite medium, the average SEM area of the agglomerates is 3000 μm 2 -50000μm 2 , for example, 3000μm 2 , 5000μm 2 , 10000μm 2 , 20000μm 2 、30000μm 2, 40000μm 2 , 50000μm 2 ;
[0021] And / or, in the cross section of the porous composite medium, the density of the agglomerates is 3-70 / 1mm 2 , for example, 3 / 1mm 2 , 10 pieces / 1mm 2 , 20 pieces / 1mm 2 、30pcs / 1mm 2 , 40 pieces / 1mm 2 , 50 pieces / 1mm 2 , 60 pieces / 1mm 2 , 70 pieces / 1mm 2 .
[0022] In the present invention, there are some small-sized agglomerates in the porous composite medium. In order to facilitate the statistics and analysis of the agglomerates in the SEM images, the SEM area is less than 500 μm. 2 The aggregates were ignored in the calculation process, and only the SEM area within 500 μm was counted. 2 Aggregates above.
[0023] Agglomerates are relatively dense areas inside porous composite media. It is the existence of agglomerates that improves the overall mechanical strength of the porous composite media. Further research has found that the area and density of agglomerates (the number within a certain area) will also affect the pore distribution of the porous composite media. When the area is too large or too small, the PMI average pore size and porosity of the porous composite media may not be able to reach the range described above, thereby affecting the various performance of the product. If the area of the agglomerates is too small or the number is too small (the density is too low), the mechanical strength (hardness and compressive strength) of the porous composite medium will still be relatively poor and will not be significantly improved; at the same time, when used in a high-pressure environment, there is still a risk of stratification inside the porous composite medium; and if the number of agglomerates is too large or the area is too large, it may also mean that the number of free fibers is reduced, which will not only easily lead to a low overall porosity of the composite medium and a smaller flux, but will also affect the interception efficiency of various impurities, reduce the pollution holding capacity, and reduce the service life of the product; therefore, agglomerates of a certain density and a certain area size can ensure that the composite medium as a whole has a higher flux and mechanical strength; at the same time, it can further efficiently intercept various impurities, have a high pollution holding capacity, and a long service life.
[0024] The SEM average area and density of the agglomerates in the present invention can be obtained by using a scanning electron microscope to characterize the morphology of the cross section of the composite medium, then selecting a certain area, the specific area size depends on the actual situation, and then using computer software (such as Matlab, NIS-Elements, etc.) or manual measurement to obtain the area and number of agglomerates in the area, and further calculation to obtain the SEM average area and corresponding density of the agglomerates.
[0025] As a further improvement of the present invention, on a cross section of the porous composite medium, with the thickness direction of the porous composite medium as the y-axis, the average SEM size d1 of the agglomerates along the y-axis is 50 μm-500 μm, for example, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm;
[0026] And / or, an average SEM size d2 perpendicular to the y-axis direction is 60 μm-800 μm, such as 60 μm, 100 μm, 200 μm, 400 μm, 600 μm, and 800 μm.
[0027] When using porous composite media for filtration, the material to be filtered often moves along the thickness direction of the composite media, that is, the filtration is carried out in the thickness direction of the composite media, so higher requirements are placed on the mechanical strength of the composite media in the thickness direction. Studies have found that when the agglomerates are flat, that is, when d1 is too small, the mechanical strength in the thickness direction is low, and when used in a high-pressure environment, the porous composite media is more likely to have a risk of stratification. The agglomerates obtained by sintering have a suitable d1 in the thickness direction, which ensures that the porous composite media is not easy to stratify internally during the filtration process, improves the interception performance and service life of the porous composite media, and has higher mechanical properties. When d1 and d2 are both within the range, the size of the agglomerates is appropriate, and the connection methods between different agglomerates inside the porous composite media are varied, so that the product has a suitable non-directional tortuous path, reduces the proportion of closed pores, and ensures that the composite media has high mechanical properties while having higher interception efficiency and dirt holding capacity, which is conducive to extending the filtration life of the porous composite media.
[0028] As a further improvement of the present invention, the ratio d1 / T of d1 to the thickness T of the porous composite medium is 1.5%-20%, such as 1.5%, 2%, 5%, 10%, 15%, 20%, preferably 2%-15%;
[0029] And / or, in the thickness direction of the cross section of the porous composite medium, the ratio of the sum of d1 of the agglomerates to the thickness T of the porous composite medium is 20%-60%, for example, 20%, 30%, 40%, 50%, 60%.
[0030] The ratio of the sum of the thickness of a single agglomerate and the thickness of agglomerates in the thickness direction to the thickness of the porous composite medium affects the size and number of agglomerates in the thickness direction. When the thickness of the porous composite medium is constant, the larger the single agglomerate, the fewer agglomerates it can accommodate. It is easy for the sum of the thickness of the agglomerates to be too large, which is not conducive to the formation of non-directional tortuous pathways, and the thickness uniformity and mechanical strength uniformity of the product will be adversely affected. When used in a high-pressure environment, there is a risk of fracture or breakage. At the same time, it will cause low porosity and the formation of closed pores, which will reduce the flux and pollution capacity of the porous composite medium and shorten the life of the porous composite medium. When the thickness of a single agglomerate accounts for too small a proportion, it is also easy to lead to the formation of closed pores, resulting in more invalid pores, which will reduce the flux and pollution capacity of the porous composite medium and shorten the life of the porous composite medium. It is also easy to cause the risk of internal stratification of the porous composite medium, and the mechanical properties of the composite medium will also be reduced. When it meets the above-mentioned range, it is conducive to the formation of non-directional tortuous passages and improves the mechanical strength of the product, thereby having a favorable effect on improving the filtering and air permeability performance of the product; at the same time, it is also conducive to improving the stability and thickness uniformity of the product, avoiding the occurrence of tearing, breaking, falling off, breakage and delamination.
[0031] As a further improvement of the present invention, the ratio of the SEM average diameter of the polymer fiber to d1 is 1:2-10, such as 1:2, 1:4, 1:6, 1:8, 1:10;
[0032] And / or, d1 / d2 is 1:1.2-8, such as 1:1.2, 1:2, 1:4, 1:6, 1:8, preferably 1:1.5-5.
[0033] The size of the polymer fiber diameter affects the formation and stability of agglomerates. For example, when the fiber diameter is too large, its mechanical strength is relatively large, and it is not easy to stick together during the sintering process. Even if agglomerates are formed, they are easy to disperse under pressure during high-pressure filtration, resulting in a short life of the composite medium. If the diameter is too small, it is easy to form overly large agglomerates, which is not conducive to the improvement of the mechanical strength, flux and dirt holding capacity of the composite medium. When the ratio of fiber diameter to agglomerate d1 meets this range, the free fibers and agglomerates can be maintained in a relatively good ratio, which is conducive to the formation of non-directional tortuous pathways. The composite medium has higher mechanical properties and higher flux and dirt holding capacity.
[0034] When d1 / d2 is within the above range, the cross-section of the agglomerate is more of a near-rectangle with a relatively small aspect ratio, which is beneficial to improving the mechanical strength of the product and the formation of non-directional tortuous pathways, reducing the generation of closed cells, and making the composite medium have good filtration performance. At the same time, when the ratio of the fiber diameter to the d1 of the agglomerate is met, the composite medium can have excellent mechanical and filtration properties, ensuring that it can maintain a high flux level for a long time during filtration, so that the product has a long service life.
[0035] As a further improvement of the present invention, the surface of the porous composite medium is tested by infrared absorption spectrum using ATR method. -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, and the ratio of the peak area of the first peak to the peak area of the second peak is the polyethylene relative peak area X, and the polyethylene relative peak area X is 0.01-4, such as 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4; the SEM average diameter of the polymer fiber is 10μm-30μm, such as 10μm, 15μm, 20μm, 25μm, 30μm.
[0036] The research found that PE in the infrared spectrum of the composite medium is 720cm -1 There is a crystallization absorption peak near the position, and its value is affected by various factors such as PE content, PE crystallization, and crystal form. The size of this value will have a great influence on the mechanical strength, heat resistance and other properties of the porous composite medium. That is, at 720cm -1 The size of the crystal absorption peak near the position can characteristically reflect the existence and content of PE in the composite medium and the PE crystallization situation to a certain extent, while the 2920cm -1 The second peak near the position is the internal standard peak (standard peak) of PE. It corresponds to the unique asymmetric stretching vibration of the methylene group of PE and can avoid the interference of absorption by polymer A. Therefore, it is used as the internal standard peak of PE. The ratio of the peak area of the first peak to the second peak reflects the relative peak area X of PE (the reason for the ratio is that the research found that only using 720cm -1The crystal absorption peak size near the position will have a great deviation, and cannot well represent the various properties of the composite medium). To a certain extent, it can reflect the comprehensive range of the PE content in the composite medium and the crystallization of PE after sintering. Furthermore, the relative peak area X of polyethylene is 0.01-4; because when X is too high or too low, it means that the content of PE present as a binder is too high or too low, and the crystallinity is too high or too low, which is not conducive to the formation of agglomerates, and the stability of the formed agglomerates will also deviate (agglomerates formed by fibers are easily separated under the high pressure). When X is within this range and at the same time satisfies the SEM average diameter of the polymer fiber of 10-30 μm, it is conducive to the formation of agglomerates of appropriate size, and the composite medium has a suitable degree of crystallinity, thereby improving the mechanical properties and filtration performance of the product.
[0037] As a further improvement of the present invention, when the polymer A comprises polypropylene, the surface of the porous composite medium is tested by infrared absorption spectrum using the ATR method. -1 -975cm -1 There is a third peak at 2940cm -1 -2960cm -1 There is a fourth peak, and the ratio of the peak area of the third peak to the peak area of the fourth peak is the relative peak area Y of polypropylene, and the relative peak area Y of polypropylene is 0.1-0.8, such as 0.1, 0.2, 0.4, 0.6, 0.8;
[0038] Preferably, X / Y is 0.01-1, such as 0.01, 0.05, 0.1, 0.5, 1.
[0039] Similar to PE, a characteristic peak in the infrared spectrum can reflect the content, crystallization and crystal form of polymer A in the composite medium. However, the characteristic absorption peaks of different polymers reflected in the infrared spectrum are different depending on the type of polymer A. Among them, for the case where polymer A contains PP, the study found that at 973cm -1 There is a crystal absorption peak near the position that can characteristically reflect the PP content and crystallization status in the composite medium. -1 The fourth peak near the position is the internal standard peak of PP, which corresponds to the unique asymmetric stretching vibration of methyl group of PP and can avoid the interference of PE absorption, so it is used as the internal standard peak of PP. Compared with the peak area of the third peak, the ratio of the peak area of the third peak to the fourth peak, that is, the relative peak area Y of PP, can more accurately reflect the content range of PP in the composite medium and the crystallization of PP after sintering.
[0040] During the research, it was also found that the values of X and Y in the composite media containing different polymers A are different. When polymer A is PP, Y is 0.1-0.8. If X and Y are too high or too low, it means that the content of PP and PE is too high or too low, and the crystallinity is too high or too low, which is not conducive to the formation of agglomerates. In addition, the mechanical properties of the composite medium deviate, and the stability of the pores will also deviate (collapse or shrinkage may occur). When X and Y meet the range, especially when X / Y is further satisfied to be 0.01-1, it is more conducive to the formation of stable agglomerates and non-directional tortuous pathways, so that the composite medium has excellent mechanical properties and filtration performance.
[0041] As a further improvement of the present invention, when the polymer A comprises polyethylene terephthalate (PET), the surface of the porous composite medium is subjected to infrared absorption spectrum test by ATR method. -1 -858cm -1 There is a fifth peak at 1709cm -1 -1729cm -1 There is a sixth peak, and the ratio of the peak area of the fifth peak to the peak area of the sixth peak is the relative peak area Z of polyethylene terephthalate, and the relative peak area Z of polyethylene terephthalate is 0.01-0.5, such as 0.01, 0.05, 0.1, 0.5; preferably, X / Z is 20-40, such as 20, 25, 30, 35, 40.
[0042] For the case where polymer A contains PET, the study found that -1 There is a crystal absorption peak near the position that can characteristically reflect the PP content and crystallization status in the composite medium. -1 The sixth peak near the position is the internal standard peak of PET, which corresponds to the unique ester carbonyl stretching vibration of PET to avoid being disturbed by PE absorption, so it is used as the internal standard peak of PET. Compared with the peak area of the fifth peak, the ratio of the peak area of the fifth peak to the sixth peak, that is, the relative peak area Z of PET, can more accurately reflect the content range of PET in the composite medium and the crystallization of PET after sintering. When PP is similar, when polymer A is PET, Z is 0.01-0.5. If X and Z are too high or too low, it means that the content of PET and PE is too high or too low, and the crystallinity is too high or too low, which is not conducive to the formation of agglomerates, and the mechanical properties of the composite medium are biased, and the stability of the pores will also be biased (collapse or shrinkage may occur). When X and Z meet the range, especially when X / Z is further satisfied to be 20-40, it is more conducive to the formation of stable agglomerates and non-directional tortuous paths, so that the composite medium has excellent mechanical properties and filtration performance.
[0043] It should be understood that during infrared testing, multiple points on the sample can be selected for testing, and then the values that deviate too much are removed and their average value is calculated.
[0044] As a further improvement of the present invention, the difference between the maximum pore size and the minimum pore size in the porous composite medium is 100nm-800nm, such as 100nm, 200nm, 400nm, 600nm, 800nm;
[0045] And / or, the thickness of the porous composite medium is 1mm-8mm, such as 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm; and / or, the DSC crystallinity of the porous composite medium is 20%-50%, such as 20%, 30%, 40%, 50%.
[0046] The difference between the maximum pore size and the minimum pore size can be measured by a PMI pore size tester; the DSC crystallinity can be measured by differential scanning calorimetry (DSC).
[0047] The porous composite medium of the present invention is a micron-sized porous composite medium, which has a wide pore size distribution when the difference between the maximum pore size and the minimum pore size is 100nm-800nm, so that the composite medium has a higher specific surface area and permeability, which helps to promote the circulation of materials in the composite medium and improve the filtration efficiency. At the same time, the porous composite medium with a wide pore size distribution can more effectively separate particles of different sizes, because larger pores can capture larger impurities, while smaller pores can intercept smaller particles, thereby improving the filtration selectivity of the porous composite medium. In addition, the larger pores can be used as a release point for stress concentration and as a buffer zone for the expansion of microcracks, which helps to disperse the stress on the porous composite medium, thereby improving its overall stability and mechanical strength, reducing wear, deformation or rupture caused by external factors (such as pressure, temperature, etc.) during use, increasing the amount of dirt, reducing clogging problems, extending the service life, and reducing maintenance costs.
[0048] For this field, as the thickness of the filter medium increases, its flux becomes lower, which is less conducive to improving the filtration rate. Therefore, the thickness of the filter medium needs to be controlled to be micron-level, usually below 500μm, and the thickness of the filter medium is not expected to reach mm level. The composite medium in the present invention has the characteristics of high porosity, so it is hoped and possible to provide a porous composite medium with a thickness of mm level to expand the application scenarios of the composite medium. The increase in thickness gives it higher mechanical strength, and at the same time, combined with a suitable pore size, it can further improve the interception efficiency of the porous composite medium; with a wider pore size distribution under thicker specifications, it can intercept particles of different sizes, increase the dirt holding capacity, have a wide range of applications, and extend the service life.
[0049] DSC crystallinity reflects to a certain extent the proportion of crystalline regions in the composite medium. The higher the DSC crystallinity, the more crystalline regions it represents, the better the degree of directional arrangement of the lattice molecules, and the better its mechanical strength. The present invention has the above-mentioned DSC crystallinity on the basis of the above-mentioned pore size and porosity, indicating that the porous composite medium does not have the problems of too high or too low crystallinity, that is, there are no problems such as low bonding strength and powder inclusion. The agglomerates in the composite medium are more tightly bonded, the non-directional tortuous pathways have better connectivity, and are not easy to delaminate. At the same time, it has higher mechanical strength, stronger heat resistance and greater porosity; when it works in conjunction with thickness, it can further improve the stability of the composite medium, and it is not easy to delaminate or slag.
[0050] As a further improvement of the present invention, the surface of the porous composite medium includes a plurality of mold wall contact areas; the SEM average width of the mold wall contact area is 30μm-200μm, such as 30μm, 50μm, 80μm, 100μm, 150μm, 200μm, preferably 50μm-150μm; the area proportion of the mold wall contact area is 20%-80%, such as 20%, 30%, 40%, 50%, 60%, 70%, 80%.
[0051] The mold wall contact zone in the present invention is formed when the raw material is melted and contacts the inner wall of the mold during the sintering process. The SEM average width of the mold wall contact zone reflects to a certain extent the size of the skeleton material on the surface of the porous composite medium. When there is a suitable skeleton foundation, it is beneficial to improve the compressive strength of the porous composite medium. At the same time, the area ratio of the mold wall contact zone represents the entity part of the contact between the raw material and the mold during the sintering process. Therefore, the area ratio of the mold wall contact zone will also affect the compressive strength of the composite medium surface during application to a certain extent. The area ratio of the mold wall contact zone = the SEM average area of the mold wall contact zone / the SEM average area of the surface of the porous composite medium, which is equivalent to 1 minus the surface hole area ratio (surface hole area ratio). When it is within this range, it can further improve the compressive strength of the porous composite medium and the surface compressive strength of the porous composite medium in various practical application conditions.
[0052] In the present invention, the relevant features of SEM can be obtained by photographing the porous composite medium using a scanning electron microscope, and then taking multiple points and measuring them separately using computer software (such as Matlab, NIS-Elements, etc.) or manually, and taking the average value; of course, it can be understood that those skilled in the art can also obtain the above parameters by other measurement methods.
[0053] As a further improvement of the present invention, the flux of the porous composite medium is 0.5-8 L / min@7 kpa, such as 0.5 L / min@7 kpa, 1 L / min@7 kpa, 2 L / min@7 kpa, 4 L / min@7 kpa, 6 L / min@7 kpa, 8 L / min@7 kpa;
[0054] and / or; the porous composite medium has a retention efficiency of greater than 95% for impurity particles with a particle size of 0.1-10 μm (preferably 0.1-5 μm), such as 95%, 96%, 97%, 98%, 99% or more;
[0055] And / or, the Shore A hardness of the porous composite medium is not less than 90HA, such as 90HA, 92HA, 96HA, 98HA;
[0056] And / or, the compressive strength of the porous composite medium is not less than 65N@1mm, such as 65N@1mm, 70N@1mm, 75N@1mm, 80N@1mm or above.
[0057] Through the interception test and the flux test, it is demonstrated that the composite medium of the present invention not only has the ability to efficiently intercept various fine impurities, but also has excellent flux.
[0058] The flux of the porous composite medium can be tested using an air permeability tester. The air pressure is adjusted to a test pressure of 7 kPa, and the corresponding flux is read and recorded (test multiple times, preferably more than 3 times, and take the average value). The air permeability area of the porous composite medium is controlled at 1 cm 2 under the conditions.
[0059] The Shore A hardness can be tested using a Shore A hardness tester, and the average value is taken after three tests.
[0060] Compression Strength of Porous Composite Media The porous composite media can be cut into arched samples with a width of 1 cm and a length of 3 cm, and placed on a compression testing machine to test the compression strength.
[0061] The porous composite medium of the present invention is a hydrophobic material, and of course, a hydrophilic material can be obtained through a suitable hydrophilic modification process as required.
[0062] A second aspect of the present invention provides a method for preparing the porous composite medium as described above, the method comprising the following steps:
[0063] (1) laminating a layered material composed of at least two layers of polymer fibers to obtain a laminated material, wherein the laminating conditions are such that the compression amount in terms of thickness is 50-80% (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%);
[0064] (2) performing a first sintering and a second sintering on the pressed material to obtain a sintered material;
[0065] (3) cooling the sintered material to obtain a porous composite medium;
[0066] The polymer fiber is composed of polyethylene and polymer A, and the polymer A comprises at least one of polypropylene, polyethylene terephthalate, polyamide, polybutylene terephthalate, and polytrimethylene terephthalate;
[0067] The conditions for the first sintering include: a temperature of 100-140° C. (for example, 100° C., 110° C., 120° C., 130° C., 140° C.), and a holding time of 10-30 min. (for example, 10 min., 15 min., 20 min., 25 min., 30 min.);
[0068] The conditions of the second sintering include: a temperature of 150-180° C. (for example, 150° C., 160° C., 170° C., 180° C.), and a holding time of 10-30 min (for example, 10 min, 15 min, 20 min, 25 min, 30 min);
[0069] The cooling conditions include: a cooling rate of 5-15°C / min (such as 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min).
[0070] The present invention can prepare the porous composite medium described in the first aspect (that is, the composite medium is sintered from multiple layered structures, including two end faces (outer surfaces)) using a layered material containing two polymer fibers through a compression and sintering method, wherein controlling the compression amount is beneficial to the bonding between the fibers and the formation of agglomerates during the sintering process, while affecting the formation of pores and porosity (excessive compression will lead to a significant decrease in the porosity of the product), which can improve the mechanical properties and physical properties of the product.
[0071] In the present invention, the compression amount (%) refers to 100% minus the thickness of the multi-layered laminated material after compression / the thickness of the multi-layered laminated material before compression.
[0072] As sintering proceeds, in the first sintering process, the PE (polyethylene) in the polymer fiber begins to melt, and gradually adheres together over time, initially forming a certain number of pores with a certain pore diameter. By controlling the time to avoid full sintering in the first sintering process, over-sintering occurs in the second sintering process, which greatly reduces the porosity; in the second sintering process, as the temperature rises and the time prolongs, the polymer will decompose, and the particles between the fibers will be rearranged and bonded, and agglomerates will be formed. Therefore, the two sintering temperatures and holding times are the key factors affecting the microstructure, which leads to changes in fiber diameter and the formation of agglomerates, which simultaneously affect the porosity and complexity. The size of the overall pore size of the composite medium; through the synergistic effect of appropriate compression and two sinterings, it is beneficial to ensure that the porous composite medium has a higher flux and mechanical strength, and the porous composite medium is not easy to stratify inside, and can perform high-pressure filtration for a long time, and efficiently capture various impurities; in addition, it has been found through research that the cooling rate during the cooling process will further cause different stresses and microstructural changes in the porous composite medium (the stability of the pores of the composite medium, the fibers are very firmly combined together to form agglomerates, and further to form agglomerates with an ideal shape in the present invention), thereby synergistically affecting the mechanical properties of the porous composite medium and having a longer service life.
[0073] Specifically, as a further improvement of the present invention, the gram weight of the layered raw material is 50-200 g / m 2 , for example 50g / m 2 , 80g / m 2 , 100g / m 2 , 120g / m 2 , 150g / m 2 , 180g / m 2 , 200g / m 2 ;
[0074] And / or, the thickness of the layered raw material is 0.1-1mm, such as 0.1mm, 0.2mm, 0.4mm, 0.6mm, 0.8mm, 1mm; and / or, the porosity of the layered raw material is 70-90%, such as 70%, 75%, 80%, 85%, 90%; and / or, the moisture content in the layered material is less than 5wt%, such as 5wt%, 4wt%, 3wt%, 2wt%, 1wt% or less, preferably less than 1wt%.
[0075] The layered material can be a conventional material in the art, such as a non-woven fabric. When selecting layered raw materials, it is found that the parameters of the layered raw materials, such as gram weight, thickness and porosity, directly affect the structural performance, filtration efficiency, mechanical strength and application performance of the final product; for example, gram weight refers to the mass of the layered raw materials per unit area, and gram weight directly affects the fiber thickness and density of the product (which will have a greater impact on the formation of agglomerates), which is a key factor in determining the strength and durability of the porous composite medium. In general, the higher the gram weight, the better the strength and impact resistance of the porous composite medium, and it can withstand greater tension and pressure (but the gram weight is too high, which will affect the filtration performance and air permeability of the product). Porosity will affect the porosity and agglomerate formation in the porous composite medium, and then affect the flux and mechanical strength of the porous composite medium, affecting practical applications. Thickness affects the mechanical stability and durability of the porous composite medium. By compressing and sintering multiple layers of raw materials of a certain thickness, a porous composite medium of ideal thickness is finally formed. At the same time, the porous composite medium is not easy to delaminate under high pressure, and there is almost no particle drop, ensuring cleanliness.
[0076] The moisture content in the layered material of the present invention can be obtained by baking the material, for example, baking the material at a temperature of 50-80°C for 0.5-2h, as long as the moisture content can reach this range. The presence of moisture will affect sintering. If the moisture content is too high, the unevenness of the pores in the composite medium will be too large, and the porosity will be too low. When the moisture content is within this range, it is beneficial to improve the uniformity of the pores in the porous composite medium and obtain a product with a larger porosity.
[0077] As a further improvement of the present invention, the number of layers of the layered raw material is 5-25, such as 5, 10, 12, 15, 18, 20 and 25, preferably 10-20;
[0078] And / or, the polymer fiber comprises a bicomponent fiber, preferably further comprises a single component fiber, and the polymer of the single component fiber is at least one of polypropylene, polyethylene terephthalate, polyamide, polybutylene terephthalate, and polytrimethylene terephthalate.
[0079] The number of layers and the composition of the polymer fibers determine the thickness of the porous composite medium and the formation of agglomerates and pores therein, and affect its stability. The combination of the two can yield a porous composite medium with appropriate thickness, agglomerates of suitable size and suitable pore size distribution.
[0080] The structure of the two-component fiber can be a conventional structure in the art, such as a skin-core structure, in which the skin layer contains PE and the core contains polymer A; or it can be a parallel structure, such as PE and polymer A are arranged side by side. The polymer fiber can also contain single-component fibers, that is, two-component fibers and single-component fibers exist at the same time, in which case a product with higher strength can be obtained. During the research, it was found that during the sintering process, after reaching the melting point of PE, the PE located in the skin layer will melt first, and the fiber diameter will become smaller after melting; due to the melting of PE, the fibers that were originally tightly entangled in the layered material will bond into larger clusters and then form agglomerates; the fibers that are not in contact with other fibers will have a smaller fiber diameter and be in a dispersed fiber state, while the polymer A in the core basically retains the original performance and shape, providing the necessary mechanical properties and modulus support for the porous composite medium.
[0081] During the research, it was found that on the basis of controlling the compression amount to 50%-80%, as a further improvement of the present invention, the conditions of the pressing treatment include: a pressure of 0.1MPa-0.6MPa, such as 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, which is conducive to controlling the interval between the layered materials, so that the arrangement between the fibers will be more compact, the contact area between the fibers will increase, which is conducive to the combination of the fibers during the sintering process, and then affect the formation of non-directional tortuous paths during the sintering process. This relatively close arrangement and combination helps to sinter to obtain suitable agglomerates and pores, thereby improving the density, strength and corrosion resistance of the product, and avoiding the subsequent sintering of the product. Layering or powder inclusion. However, further increase in compression and excessive pressure will also lead to a decrease in the porosity of the product. Too low porosity may also affect the flux and interception efficiency of the product. If the compression amount is too low or the pressure is too small, it will affect the subsequent sintering process, resulting in a decrease in the crystallinity of the porous composite medium and the presence of powder inclusion.
[0082] Sintering temperature is a key factor affecting the microstructure of porous composite media. Holding time affects the degree of sintering, the diameter and fracture degree of fibers, and thus the formation of agglomerates. During the experiment, it was found that as the sintering temperature increased, the polyethylene with a lower melting point began to melt, and the fibers began to bond together, gradually forming a sintering neck that gradually increased with time. The fibers became more tightly bonded, and agglomerates were formed during the secondary sintering process.
[0083] During the first sintering, controlling the temperature range and keeping it warm for a period of time can make the temperature distribution of the polymer fiber more uniform, which is conducive to the melting of PE and the skeleton distribution of polymer A. During the first sintering process, PE melts and initially bonds, but basically polymer A does not melt, which is conducive to the subsequent sintering to obtain holes and agglomerates with ideal pore sizes and numbers, avoiding excessive sintering or powder inclusion, stratification and other phenomena. If the temperature is too low, the melting adhesion of PE cannot be achieved, which is not conducive to the subsequent formation of agglomerates. If the temperature is too high, it will easily lead to over-sintering during the second sintering process, causing excessive decomposition of the polymer, and significantly thinning the fiber diameter. As a further improvement of the present invention, the heating rate of the first sintering is 10-15°C / min, such as 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, and 15°C / min. Such a heating rate not only ensures efficiency, but also prevents the temperature difference between different polymer fibers from being too large, which is conducive to the subsequent sintering process.
[0084] The temperature of the second sintering is controlled at 150-180°C. At such a temperature, the surfaces of the polymer fibers that have already bonded to each other will further fuse with each other due to the movement and diffusion of the molecular segments, and stably and firmly connect together; combined with the control of the insulation time, a suitable non-directional tortuous path can be generated while forming a suitable agglomerate, and finally an ideal porous composite medium is formed. If the temperature is too low or the time is too short, it is not conducive to the formation of agglomerates. If the temperature is too high or the time is too long, it will be over-sintered, resulting in a significant reduction in the number of pores. The porosity and flux of the final composite medium are too low, and the mechanical strength is poor. As a further improvement of the present invention, the heating rate of the second sintering is 5-10°C / min, such as 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min. When the heating rate is within this range, the sintering process can be carried out smoothly, avoiding problems such as excessive temperature gradient and stress concentration caused by too fast heating. The heating rate of the first sintering may be greater than the heating rate of the second sintering, which is beneficial to further alleviate problems such as excessive temperature gradient and stress concentration.
[0085] Moreover, the study found that if only the first sintering is performed, only sintering necks may be formed between the fibers without obvious fusion, and agglomerates cannot be formed in the obtained porous composite medium; if only the second sintering is performed, the melting of PE can cause obvious fusion between the fibers, but there will be over-sintering, powder inclusion, etc., and the polymer fiber is prone to diameter shrinkage and fracture, both of which are not conducive to the formation of agglomerates and pores, and the mechanical properties and filtration properties of the prepared porous composite medium are poor. In addition, if the sintering temperature is too high, it may cause the melting of polymer A, resulting in the shrinkage of the fiber diameter or the fracture of the fiber, and even micropores, cracks or granular structures, which are not conducive to the formation of agglomerates and problems such as the diameter of free fibers being too thin, thereby affecting the filtration performance and mechanical properties of the porous composite medium. When the sintering temperature is too high, it may also lead to excessive sintering, cracks, deformation and other problems, which will reduce the performance of the product.
[0086] During the research process, it was also found that even if the compression amount and secondary sintering process were controlled, the crystallinity cooling rate in the obtained composite medium may still cause different stresses and microstructural changes inside the product. Sudden cooling can reduce the crystallinity and hardness of the porous composite medium and improve the tensile strength; while slow cooling may make the crystallization of the porous composite medium more perfect, but may reduce its toughness. When the cooling rate is 5-15℃ / min, the crystallinity of the porous composite medium is controlled within an appropriate range, the agglomerates in the composite medium are more tightly bonded, the non-directional tortuous pathways have better connectivity, and are not easy to stratify, which is conducive to making the porous composite medium have both good toughness and tensile strength.
[0087] A third aspect of the present invention provides the use of the porous composite medium as described above as a porous filtration medium for liquid filtration or gas filtration.
[0088] The porous composite medium of the present invention has the characteristics of high porosity and strong chemical and physical tolerance, and can be used as a porous filter medium. Among them, liquid filtration can be used to filter solid particles or suspended matter in liquids, such as in water treatment (such as in microfiltration, ultrafiltration and reverse osmosis systems, for water purification and seawater desalination), oil filtration, chemical processing, food and beverage industry (such as for filtering beverages, beer, juice, etc., to remove impurities and microorganisms), fine chemical industry (such as in the production process of cosmetics and personal care products, for filtering emulsions, pastes and other products), pharmaceutical industry (such as for removing impurities), electronic product manufacturing industry (can be used to filter chemical cleaning agents, detergents and ultrapure water), mining and mineral processing (for filtering mineral slurries and tailings), agriculture (can be used to filter irrigation water, remove soil particles and other impurities).
[0089] Gas filtration can be used in the chemical and manufacturing industries to remove harmful gases or vapors, such as acid gases, solvent vapors, and other harmful emissions. Or as a filter medium in air purification systems, in heating, ventilation, and air conditioning systems (HVAC), it is used to improve indoor air quality and remove odors, bacteria, and viruses. It can also be used in medical equipment, such as in ventilators, anesthesia machines, and other medical equipment to provide sterile air or filter out the air exhaled by patients. In the automotive industry, it can also be used in automobile emission control systems to reduce pollutant emissions in exhaust gas. In the painting and coating industry, it can be used for air filtration in paint booths to remove excess paint particles and dust. In the nuclear industry, it can be used to filter radioactive gases and dust to protect the environment and worker safety. It can be used in fragrance diffusers and air fresheners to control the release of fragrance. In various industrial processes, it is used to collect and filter the dust generated to protect the working environment and reduce pollution.
[0090] The present invention adopts the above technical solution to achieve the following beneficial effects:
[0091] The porous composite medium described in the present invention is obtained by sintering polymer fibers containing at least two polymers. It has the advantages of high flux and high mechanical properties, and has the advantages of high filtration efficiency, long life, corrosion resistance, high temperature resistance, etc. Its unique porous structure and material properties enable it to maintain stable filtration performance in various harsh environments.
[0092] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] Figure 1 Shown is a SEM image of a longitudinal section perpendicular to the end surface of the porous composite medium prepared in Example 1 of the present invention, wherein the magnification is 50×.
[0094] Figure 2 Shown is a SEM image of one end surface of the porous composite medium prepared in Example 1 of the present invention, where the magnification is 100×.
[0095] Figure 3 Shown is a SEM image of a longitudinal section perpendicular to the end surface of the porous composite medium prepared in Example 2 of the present invention, wherein the magnification is 100×.
[0096] Figure 4Shown is a SEM image of a longitudinal section perpendicular to the end face of the porous composite medium prepared in Example 6 of the present invention, where the magnification is 100×. DETAILED DESCRIPTION
[0097] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0098] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0099] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0100] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0101] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0102] Example 1
[0103] This embodiment provides a method for preparing the porous composite medium described in the present invention.
[0104] S1. Heat and dry the nonwoven fabric composed of polymer fibers at a temperature of 70°C for 1 hour, so that the moisture content in the nonwoven fabric is less than 1 wt%. The weight of the nonwoven fabric is 130 g / m 2 The single layer thickness is 0.7 mm and the porosity is 75%. The polymer fiber is a skin-core structure, with the skin being PE and the core being PP.
[0105] S2. Cut the non-woven fabric treated in S1 to obtain neat and regular non-woven fabric sheets, take 16 layers of sheets and lay them flat into the board sintering mold. The sheets are required to be flat and wrinkle-free. Close the pressing mold and perform pressing treatment. The pressure is controlled to 0.4Mpa, and the compression amount measured by thickness is 65%.
[0106] S3. Place the sintering mold flatly in the sintering equipment, set the first sintering process parameters, start heating from room temperature, set the heating rate to 12°C / min, the first sintering temperature to 130°C, and the insulation time to 20min; then set the second sintering process parameters, set the heating rate to 8°C / min, the temperature to 165°C, and the insulation time to 20min.
[0107] S4. After sintering, it automatically enters the cooling device, and the cooling rate is set to 10℃ / min. After cooling to room temperature, the mold is opened by the mold opening device, and the sintered fiber board is taken out. The fiber board is placed flat in the punching equipment, and a specific punching die is used to punch it into the required specifications, which is the porous composite medium.
[0108] The SEM image of the prepared porous composite medium is shown in Figure 1 As shown in the figure, from Figure 1 It can be seen that there are several agglomerates formed by sintering the polymer fibers in the porous composite medium. The agglomerates are connected to each other, and there are free fibers around the agglomerates. Fibers can also be seen inside the agglomerates. In the cross section of the porous composite medium, the agglomerates are rectangular or circular. Figure 2 As shown, the surface of the porous composite medium includes a plurality of mold wall contact areas, and the average SEM width of the mold wall contact areas is in the range of 50 μm-150 μm; the area proportion of the mold wall contact areas is in the range of 20%-80%.
[0109] The thickness T of the prepared porous composite medium was measured to be 3.8 mm, the average fiber SEM diameter was 20 μm, the average PMI pore size was 1.5 μm, the difference between the maximum pore size and the minimum pore size was 500 nm, the porosity was 60%, and the average SEM area of the agglomerates in the thickness direction of the cross section of the porous composite medium was 25,000 μm. 2 , density is 24 pieces / mm 2 , d1 is 150μm, d2 is 200μm, d1 / d2 is 1:1.33, d1 / T is 3.95%, the ratio of the sum of d1 of agglomerates to T is 38.6%, and the fiber SEM average diameter / d1 is 1:7.5.
[0110] The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, and the relative peak area X of polyethylene is 0.23; at 965cm -1 -985cm-1 There is a third peak at 2940cm -1 -2960cm -1 There is a fourth peak, the ratio of the peak area of the third peak to the peak area of the fourth peak is the relative peak area of polypropylene Y, the relative peak area of polypropylene Y is 0.38; X / Y is 0.61. The DSC crystallinity of the porous composite medium is 36%.
[0111] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0112] Example 2
[0113] This embodiment provides a method for preparing the porous composite medium described in the present invention.
[0114] S1. Heat and dry the nonwoven fabric composed of polymer fibers at a temperature of 70°C for 1 hour, so that the moisture content in the nonwoven fabric is less than 1 wt%. The weight of the nonwoven fabric is 180 g / m 2 The single layer thickness is 1 mm and the porosity is 70%. The polymer fiber is a skin-core structure, with the skin layer being PE and the core being PET.
[0115] S2. Cut the non-woven fabric treated in S1 to obtain neat and regular non-woven fabric sheets, take 12 layers of sheets and lay them flat into the board sintering mold. The sheets are required to be flat and wrinkle-free. Close the pressing mold and perform pressing treatment. The pressure is controlled to 0.6Mpa, and the compression amount measured by thickness is 80%.
[0116] S3. Place the sintering mold flatly in the sintering equipment, set the first sintering process parameters, start heating from room temperature, set the heating rate to 11°C / min, the first sintering temperature to 140°C, and the insulation time to 25min; then set the second sintering process parameters, set the heating rate to 6°C / min, the temperature to 180°C, and the insulation time to 30min.
[0117] S4. After sintering, it automatically enters the cooling device, and the cooling rate is set to 8℃ / min. After cooling to room temperature, the mold is opened by the mold opening device, and the sintered fiber board is taken out. The fiber board is placed flat in the punching equipment, and a specific punching die is used to punch it into the required specifications, which is the porous composite medium.
[0118] The SEM image of the longitudinal section of the prepared porous composite medium is as follows: Figure 3As shown in the figure, it can be seen that there are several agglomerates formed by sintering the polymer fibers in the porous composite medium, and the agglomerates are connected to each other. There are free fibers around the agglomerates, and fibers can also be seen inside the agglomerates. In the cross section of the porous composite medium, a single agglomerate is similar to a rectangle. The surface of the porous composite medium includes several mold wall contact areas, and the average SEM width of the mold wall contact area is in the range of 50μm-150μm; the area of the mold wall contact area accounts for 20%-80%.
[0119] The thickness T of the prepared porous composite medium was measured to be 2.2 mm, the average fiber SEM diameter was 35 μm, the average PMI pore size was 0.3 μm, the difference between the maximum pore size and the minimum pore size was 150 nm, the porosity was 45%, and the average SEM area of the agglomerates in the thickness direction of the cross section of the porous composite medium was 37,000 μm. 2 , density is 15 pieces / mm 2 , d1 is 150 μm, d1 / T is 9.09%, the ratio of the sum of d1 of agglomerates to T is 58.5%, and the fiber SEM average diameter / d1 is 1:5.7.
[0120] The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, and the relative peak area X of polyethylene is 2.23; at 838cm -1 -858cm -1 There is a fifth peak at 1709cm -1 -1729cm -1 There is a sixth peak, the ratio of the peak area of the fifth peak to the peak area of the sixth peak is the relative peak area Z of polyethylene terephthalate, the relative peak area Z of polyethylene terephthalate is 0.084; X / Z is 26.5. The DSC crystallinity of the porous composite medium is 48%.
[0121] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0122] Example 3
[0123] This embodiment provides a method for preparing the porous composite medium described in the present invention.
[0124] S1. Heat and dry the nonwoven fabric composed of polymer fibers at a temperature of 70°C for 1 hour, so that the moisture content in the nonwoven fabric is less than 1 wt%. The weight of the nonwoven fabric is 60 g / m 2 The single layer thickness is 0.4 mm and the porosity is 85%. The polymer fiber is a skin-core structure, with the skin being PE and the core being PBT.
[0125] S2. Cut the non-woven fabric treated in S1 to obtain neat and regular non-woven fabric sheets, take 20 layers of sheets and lay them flat into the board sintering mold. The sheets are required to be flat and wrinkle-free. Close the pressing mold and perform pressing treatment. The pressure is controlled to 0.2Mpa, and the compression amount measured by thickness is 50%.
[0126] S3. Place the sintering mold flatly in the sintering equipment, set the first sintering process parameters, start heating from room temperature, set the heating rate to 14°C / min, the first sintering temperature to 110°C, and the insulation time to 15min; then set the second sintering process parameters, set the heating rate to 10°C / min, the temperature to 150°C, and the insulation time to 15min.
[0127] S4. After sintering, it automatically enters the cooling device, and the cooling rate is set to 14℃ / min. After cooling to room temperature, the mold is opened by the mold opening device, and the sintered fiber board is taken out. The fiber board is placed flat in the punching equipment, and a specific punching die is used to punch it into the required specifications, which is the porous composite medium.
[0128] There are several agglomerates formed by sintering the polymer fibers in the porous composite medium, and the agglomerates are connected to each other. There are free fibers around the agglomerates, and fibers can also be seen inside the agglomerates. In the cross section of the porous composite medium, a single agglomerate is similar to a rectangle. The surface of the porous composite medium includes several mold wall contact areas, and the average SEM width of the mold wall contact area is in the range of 50μm-150μm; the area of the mold wall contact area accounts for 20%-80%.
[0129] The thickness T of the prepared porous composite medium was measured to be 3.8 mm, the average fiber SEM diameter was 10 μm, the average PMI pore size was 3.5 μm, the difference between the maximum pore size and the minimum pore size was 750 nm, the porosity was 75%, and the average SEM area of the agglomerates in the thickness direction of the cross section of the porous composite medium was 8,000 μm. 2 , density is 45 pieces / mm 2 , d1 is 80 μm, d1 / T is 2.11%, the ratio of the sum of d1 of agglomerates to T is 25.9%, and the fiber SEM average diameter / d1 is 1:8.
[0130] The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, the relative peak area X of polyethylene is 0.75, and the DSC crystallinity of the porous composite medium is 30%.
[0131] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0132] Example 4
[0133] This embodiment provides a method for preparing the porous composite medium described in the present invention.
[0134] S1. Heat and dry the nonwoven fabric composed of polymer fibers at a temperature of 70°C for 1 hour, so that the moisture content in the nonwoven fabric is less than 1 wt%. The weight of the nonwoven fabric is 90 g / m 2 The single layer thickness is 0.8 mm and the porosity is 80%. The polymer fiber is a skin-core structure, with the skin layer being PE and the core being PP.
[0135] S2. Cut the non-woven fabric treated in S1 to obtain neat and regular non-woven fabric sheets, take 18 layers of sheets and lay them flat into the board sintering mold. The sheets are required to be flat and wrinkle-free. Close the pressing mold and perform pressing treatment. The pressure is controlled to 0.3Mpa, and the compression amount measured by thickness is 60%.
[0136] S3. Place the sintering mold flatly in the sintering equipment, set the first sintering process parameters, start heating from room temperature, set the heating rate to 13°C / min, the first sintering temperature to 120°C, and the insulation time to 20min; then set the second sintering process parameters, set the heating rate to 8°C / min, the temperature to 155°C, and the insulation time to 20min.
[0137] S4. After sintering, it automatically enters the cooling device, and the cooling rate is set to 6℃ / min. After cooling to room temperature, the mold is opened by the mold opening device, and the sintered fiber board is taken out. The fiber board is placed flat in the punching equipment, and a specific punching die is used to punch it into the required specifications, which is the porous composite medium.
[0138] There are several agglomerates formed by sintering the polymer fibers in the porous composite medium, and the agglomerates are connected to each other. There are free fibers around the agglomerates, and fibers can also be seen inside the agglomerates. In the cross section of the porous composite medium, a single agglomerate is similar to a rectangle. The surface of the porous composite medium includes several mold wall contact areas, and the average SEM width of the mold wall contact area is in the range of 50μm-150μm; the area of the mold wall contact area accounts for 20%-80%.
[0139] The thickness T of the prepared porous composite medium was measured to be 5.5 mm, the average fiber SEM diameter was 27 μm, the average PMI pore size was 2.4 μm, the difference between the maximum pore size and the minimum pore size was 600 nm, the porosity was 68%, and the average SEM area of the agglomerates in the thickness direction of the cross section of the porous composite medium was 14,000 μm. 2 , density is 37 pieces / mm 2 , d1 is 130 μm, d1 / T is 2.36%, the ratio of the sum of d1 of agglomerates to T is 30.3%, and the fiber SEM average diameter / d1 is 1:4.8.
[0140] The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, the relative peak area X of polyethylene is 0.48, and the DSC crystallinity of the porous composite medium is 33%.
[0141] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0142] Example 5
[0143] This embodiment provides a method for preparing the porous composite medium described in the present invention.
[0144] The method described in Example 1 was followed, except that the polymer fibers of the nonwoven fabric were bicomponent fibers and monocomponent fibers, wherein the bicomponent fibers were of a sheath-core structure with the sheath being PE and the core being PP, and the monocomponent fibers were PP.
[0145] The porous composite medium contains a number of agglomerates formed by sintering the polymer fibers, the agglomerates are connected, there are free fibers around the agglomerates, and fibers can also be seen inside the agglomerates. In the cross section of the porous composite medium, the agglomerates are rectangular or circular. The surface of the porous composite medium contains a number of mold wall contact areas, the average SEM width of the mold wall contact areas is in the range of 50μm-150μm; the area of the mold wall contact areas accounts for 20%-80%.
[0146] The thickness T of the prepared porous composite medium was measured to be 3.7 mm, the average fiber SEM diameter was 24 μm, the average PMI pore size was 1.5 μm, the difference between the maximum pore size and the minimum pore size was 600 nm, the porosity was 59%, and the average SEM area of the agglomerates in the thickness direction of the cross section of the porous composite medium was 28,000 μm. 2 , density is 22 pieces / mm 2 , d1 is 170μm, d2 is 220μm, d1 / d2 is 1:1.29, d1 / T is 4.59%, the ratio of the sum of d1 of agglomerates to T is 40.5%, and the fiber SEM average diameter / d1 is 1:7.1.
[0147] The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, and the relative peak area X of polyethylene is 0.19; at 965cm -1 -985cm -1 There is a third peak at 2940cm -1 -2960cm -1 There is a fourth peak, the ratio of the peak area of the third peak to the peak area of the fourth peak is the relative peak area of polypropylene Y, the relative peak area of polypropylene Y is 0.47; X / Y is 0.40. The DSC crystallinity of the porous composite medium is 38%.
[0148] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1. The addition of the single-component fiber significantly improved the Shore A hardness and compressive strength of the porous composite medium.
[0149] Example 6
[0150] This example is used to illustrate the preparation method of the porous composite medium described in the present invention.
[0151] The operation was carried out in accordance with the method described in Example 1, except that the heating rates of the first sintering and the second sintering were both 20° C. / min.
[0152] The SEM image of the prepared porous composite medium is shown in Figure 4 As shown in the figure, the area of the prepared agglomerates is relatively small, and the average SEM area is 2000 μm 2 In the cross section of the porous composite medium, with the thickness direction of the porous composite medium as the y-axis, the average SEM size d1 of the agglomerates along the y-axis is 62 μm.
[0153] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0154] Example 7
[0155] This example is used to illustrate the preparation method of the porous composite medium described in the present invention.
[0156] The operation was carried out in accordance with the method described in Example 1, except that the heating rates of the first sintering and the second sintering were 5° C. / min and 2° C. / min, respectively.
[0157] The porosity of the prepared porous composite medium is 43%.
[0158] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0159] Example 8
[0160] This example is used to illustrate the preparation method of the porous composite medium described in the present invention.
[0161] The operation was carried out in accordance with the method described in Example 1, except that the thickness of the nonwoven fabric was 1.4, the number of layers was 8, and the pressure during the lamination process was 0.05 MPa.
[0162] The prepared porous composite medium has a d1 of 80 μm and a d2 of 400 μm.
[0163] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0164] Example 9
[0165] This example is used to illustrate the preparation method of the porous composite medium described in the present invention.
[0166] The operation was carried out in accordance with the method described in Example 1, except that the thickness of the nonwoven fabric was 0.7, the number of layers was 20, and the holding time of the second sintering was 5 minutes.
[0167] The thickness T of the prepared porous composite medium is 8.9 mm, d1 is 110 μm, and d1 / T is 1.24%.
[0168] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0169] Example 10
[0170] This example is used to illustrate the preparation method of the porous composite medium described in the present invention.
[0171] The operation was carried out in accordance with the method described in Example 1, except that the conditions for heating the material were such that the moisture content in the non-woven fabric material was below 3 wt %, and the holding time for the first sintering was 5 min.
[0172] The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, the relative peak area X of polyethylene is 0.009, and nearly 20% of the products in the batch have a certain degree of powder loss.
[0173] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 1.
[0174] Table 1
[0175] Group Flux L / min@7kpa Retention efficiency Shore A hardness / HA Compression strength / N Example 1 4 For 1μm particles, more than 95% 95 72 Example 2 1 More than 95% of 0.1μm particles 97 74 Example 3 6.5 For 3μm particles, more than 95% 92 68 Example 4 5 For 2μm particles, more than 95% 94 70 Example 5 3.9 For 1μm particles, more than 95% 99 81 Example 6 3.1 More than 90% for 1μm 90 67 Example 7 3.3 More than 90% for 1μm 94 70 Example 8 2.9 More than 90% for 1μm 90 69 Example 9 3.4 More than 90% for 1μm 92 67 Example 10 2.4 More than 90% for 1μm 91 66
[0176] Comparative Example 1
[0177] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0178] The method described in Example 1 is followed, except that the polymer fiber is made of PP.
[0179] After the experiment, it was found that the porous composite medium did not contain agglomerates, was easy to stratify, and had low mechanical strength.
[0180] Comparative Example 2
[0181] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0182] The method described in Example 1 is followed, except that the polymer fiber is made of PE.
[0183] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0184] Comparative Example 3
[0185] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0186] The operation was carried out according to the method described in Example 1, except that the pressure was controlled to be 0.8 MPa and the compression amount was 95% during the pressing process. It was found that the porosity of the prepared porous composite medium was low, which was 29%.
[0187] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0188] Comparative Example 4
[0189] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0190] The operation was carried out in accordance with the method described in Example 1, except that the pressure during the pressing process was controlled to be 0.05 MPa and the compression amount was 30%.
[0191] The results show that the average pore size of the prepared porous composite medium is 7.3 μm, the porosity is high, 72%, the agglomerates are too small and easy to delaminate.
[0192] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0193] Comparative Example 5
[0194] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0195] The method described in Example 1 was followed, except that the weight of the nonwoven fabric was 400 g / m 2 The first sintering temperature is 150°C and the holding time is 50 minutes.
[0196] The results showed that the average fiber SEM diameter of the prepared porous composite medium was 78 μm.
[0197] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0198] Comparative Example 6
[0199] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0200] The method described in Example 1 was followed, except that the weight of the nonwoven fabric was 30 g / m 2 , no first sintering was performed, and the cooling rate was 18°C / min.
[0201] The results showed that the average fiber SEM diameter of the prepared porous composite medium was 4 μm.
[0202] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0203] Comparative Example 7
[0204] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0205] The operation was carried out in accordance with the method described in Example 1, except that the temperature of the second sintering was 190° C. and the holding time was 50 min.
[0206] The results show that the average pore size of the prepared porous composite medium is 0.6 μm and the porosity is 35%.
[0207] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0208] Comparative Example 8
[0209] This comparative example is used to illustrate the preparation method of a reference porous composite medium.
[0210] The operation was carried out in accordance with the method described in Example 1, except that the temperature of the second sintering was 140° C. and the holding time was 2 min.
[0211] The results show that the average pore size of the prepared porous composite medium is 5.2 μm, the porosity is 71%, and there are basically no agglomerates and it is easy to delaminate.
[0212] The performance of the prepared porous composite medium was evaluated, and the results are shown in Table 2.
[0213] Table 2
[0214] Group Flux L / min@7kpa Shore A hardness / HA Compression strength / N Example 1 4 95 72 Comparative Example 2 0.4 64 38 Comparative Example 3 0.5 85 59 Comparative Example 4 6.7 66 41 Comparative Example 5 0.7 / / Comparative Example 6 / 56 35 Comparative Example 7 0.8 / / Comparative Example 8 / 69 43
[0215] Note: / indicates not determined.
[0216] It should be noted that, in this article, the term "comprises", "includes" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "including one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0217] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A porous composite medium, characterized in that: The porous composite medium comprises polymer fibers for forming a porous structure, wherein the polymers constituting the polymer fibers comprise polyethylene and polymer A, wherein the polymer A comprises at least one of polypropylene, polyethylene terephthalate, polyamide, polybutylene terephthalate, and polytrimethylene terephthalate, and the SEM average diameter of the polymer fibers is 5 μm-40 μm; The porous composite medium contains a plurality of agglomerates formed by sintering the polymer fibers; The PMI average pore size of the porous composite medium is 0.1 μm-5 μm, and the porosity is 40%-80%.
2. The porous composite medium according to claim 1, characterized in that: The SEM average diameter of the polymer fiber is 8 μm-35 μm; And / or, the PMI average pore size of the porous composite medium is 0.3 μm-3.5 μm; And / or, the porosity of the porous composite medium is 45%-75%.
3. The porous composite medium according to claim 1, characterized in that: In the cross section of the porous composite medium, the average SEM area of the agglomerates is 3000 μm 2 -50000μm 2 ; And / or, in the cross section of the porous composite medium, the density of the agglomerates is 3-70 / 1mm 2 .
4. The porous composite medium according to claim 3, characterized in that: On the cross section of the porous composite medium, with the thickness direction of the porous composite medium as the y-axis, the average SEM size d1 of the agglomerates along the y-axis is 50 μm-500 μm; And / or, an average SEM size d2 perpendicular to the y-axis direction is 60 μm-800 μm.
5. The porous composite medium according to claim 4, characterized in that: The ratio d1 / T of d1 to the thickness T of the porous composite medium is 1.5%-20%, preferably 2%-15%; And / or, in the thickness direction of the cross section of the porous composite medium, the ratio of the sum of d1 of the agglomerates to the thickness T of the porous composite medium is 20%-60%.
6. The porous composite medium according to claim 4 or 5, characterized in that: The ratio of the SEM average diameter of the polymer fiber to d1 is 1:2-10; And / or, d1 / d2 is 1:1.2-8, preferably 1:1.5-5.
7. The porous composite medium according to any one of claims 1 to 6, characterized in that: The surface of the porous composite medium was tested by infrared absorption spectrum at 710 cm -1 -730cm -1 There is a first peak at 2910 cm -1 -2930cm -1 There is a second peak, the ratio of the peak area of the first peak to the peak area of the second peak is the relative peak area X of polyethylene, and the relative peak area X of polyethylene is 0.01-4; the SEM average diameter of the polymer fiber is 10μm-30μm.
8. The porous composite medium according to claim 7, characterized in that: When the polymer A comprises polypropylene, the surface of the porous composite medium is subjected to infrared absorption spectrum test by ATR method. -1 -985cm -1 There is a third peak at 2940cm -1 -2960cm -1 There is a fourth peak, the ratio of the peak area of the third peak to the peak area of the fourth peak is the relative peak area Y of polypropylene, and the relative peak area Y of polypropylene is 0.1-0.8; Preferably, X / Y is 0.01-1.
9. The porous composite medium according to claim 7, characterized in that: When the polymer A comprises polyethylene terephthalate, the surface of the porous composite medium is tested by infrared absorption spectrum using the ATR method. -1 -858cm -1 There is a fifth peak at 1709cm -1 -1729cm -1 There is a sixth peak, the ratio of the peak area of the fifth peak to the peak area of the sixth peak is the relative peak area Z of polyethylene terephthalate, and the relative peak area Z of polyethylene terephthalate is 0.01-0.5; Preferably, X / Z is 20-40.
10. The porous composite medium according to any one of claims 1 to 9, characterized in that: The difference between the maximum pore size and the minimum pore size in the porous composite medium is 100-800 nm; And / or, the thickness of the porous composite medium is 1 mm-8 mm; And / or, the DSC crystallinity of the porous composite medium is 20%-50%.
11. The porous composite medium according to any one of claims 1 to 10, characterized in that: The surface of the porous composite medium comprises a plurality of mold wall contact areas; the SEM average width of the mold wall contact areas is 30 μm-200 μm, preferably 50 μm-150 μm; the area proportion of the mold wall contact areas is 20%-80%.
12. The porous composite medium according to any one of claims 1 to 11, characterized in that: The flux of the porous composite medium is 0.5-8L / min@7kpa; And / or; The interception efficiency of the porous composite medium for impurity particles with a particle size of 0.1-10 μm is greater than 95%; and / or, the Shore A hardness of the porous composite medium is not less than 90HA; And / or, the compressive strength of the porous composite medium is not less than 65N@1mm.
13. A method for preparing a porous composite medium according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: (1) laminating a layered material composed of at least two layers of polymer fibers to obtain a laminated material, wherein the laminating conditions are such that the compression amount in terms of thickness is 50-80%; (2) performing a first sintering and a second sintering on the pressed material to obtain a sintered material; (3) cooling the sintered material to obtain a porous composite medium; The polymer fiber is composed of polyethylene and polymer A, and the polymer A comprises at least one of polypropylene, polyethylene terephthalate, polyamide, polybutylene terephthalate, and polytrimethylene terephthalate; The first sintering conditions include: a temperature of 100-140°C and a heat preservation time of 10-30 minutes; The conditions of the second sintering include: a temperature of 150-180°C and a holding time of 10-30 minutes; The cooling conditions include: a cooling rate of 5-15°C / min.
14. The method according to claim 13, characterized in that The gram weight of the layered raw material is 50-200g / m 2 ; and / or, the thickness of the layered raw material is 0.1-1 mm; and / or, the porosity of the layered raw material is 70-90%; And / or, the moisture content in the layered material is 5 wt% or less, preferably 1 wt% or less.
15. The method according to claim 13 or 14, characterized in that The number of layers of the layered raw material is 5-25, preferably 10-20; and / or, the polymer fiber comprises a bicomponent fiber, the bicomponent fiber comprising a sheath-core structure; Preferably, the polymer fiber further comprises a single component fiber, and the polymer of the single component fiber is at least one of polypropylene, polyethylene terephthalate, polyamide, polybutylene terephthalate, and polytrimethylene terephthalate.
16. The method according to any one of claims 13 to 15, characterized in that: The conditions of the pressing process include: a pressure of 0.1MPa-0.6MPa; and / or, the heating rate of the first sintering is 10-15° C. / min; And / or, the heating rate of the second sintering is 5-10° C. / min.
17. Use of the porous composite medium according to any one of claims 1 to 12 as a porous filter medium for liquid filtration or gas filtration.
Citation Information
Patent Citations
Nanofibre hyperfiltration membrane and preparation method thereof
CN101559326A
Microporous filter medium
CN102553353A
Bi-component polyester coarse fibre, filter material and preparation thereof
CN101302659A
Filter media and methods of manufacturing thereof
CN105358230A
Filter medium, method for producing filter medium, water treatment module, and water treatment device
CN106659948A